KEDUDUKAN HUKUM OBJEK JAMINAN HAK TANGGUNGAN YANG DILETAKKAN SITA JAMINAN OLEH PENGADILAN DALAM PUTUSAN NOMOR 43/Pdt.Bth/2023/PN Skh - Dewi, Khoirunnisa Mustika; Aldyan, Arsyad (Verstek, 2025)
This article analyzes the legal position of a Mortgage Right guarantee object that is subsequently placed under a security seizure by the court in Decision Number 43/Pdt.Bth/2023/PN Skh. The purpose of this article is to further examine the legal position of the Mortgage Right Guarantee object as a guarantee whose holder is prioritized by law based on Law Number 4 of 1996 concerning Mortgage Rights. The findings prove that the Mortgage Right holder, as a separate creditor, has precedence in carrying out the execution of its object compared to other creditors. However, if a security seizure is placed by the court on the Mortgage Right object, the law does not explicitly regulate the legal position of the guarantee object. The jurisprudence of the Supreme Court of the Republic of Indonesia, in this case, provides legal certainty regarding this issue, thereby reaffirming the legal position of the Mortgage Right guarantee object that is placed under a security seizure.